2017
DOI: 10.1242/jeb.166405
|View full text |Cite
|
Sign up to set email alerts
|

Silica-induced fibrosis: an ancient response from the early metazoans

Abstract: Exposure to crystalline silica particles causes silicosis, an occupational disease leading to an overproduction of collagen in the lung. The first step of this pathology is characterized by the release of inflammatory mediators. Tumour necrosis factor (TNF) is a pro-inflammatory cytokine directly involved in silica-induced pulmonary fibrosis. The marine demosponge is able to incorporate silica grains and partially dissolve the crystalline forms apparently without toxic effects. In the present work, tissue expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…This again suggests that F2 may not be optimal for subsequent scaffolding procedures. Conversely, a low-diameter fibrillar organization was observable in F1, F3, and F4 PicroS staining, with the bigger collagen bundles that are typically present in C. reniformis native tissues [ 66 ] being completely removed during the first centrifugation steps.…”
Section: Discussionmentioning
confidence: 99%
“…This again suggests that F2 may not be optimal for subsequent scaffolding procedures. Conversely, a low-diameter fibrillar organization was observable in F1, F3, and F4 PicroS staining, with the bigger collagen bundles that are typically present in C. reniformis native tissues [ 66 ] being completely removed during the first centrifugation steps.…”
Section: Discussionmentioning
confidence: 99%
“…They were then synthesised by TibMolBiol (Genova, Italy). The primer sequences for GAPDH, fibrillar collagen and non-fibrillar collagen were reported in Pozzolini et al (2016a,b), while primers for proline-4 hydroxylase (P4H) and Bcl-2 were reported in Pozzolini et al (2017). The TGF1, TGF2, TGF3, TGF4, TGF5, TGF6, TGFR1, TGFR2, Piwi and Msi-1 primer sequences are presented in Table S1.…”
Section: Archeocyte Identification By Immunostainingmentioning
confidence: 99%
“…Newly synthesized tropocollagen in C. reniformis RTEs was assayed with a colorimetric method using the Sircol Assay (Biocolor Ltd, Carrickfergus, County Antrim, UK), as previously described (Pozzolini et al, 2017). The collagen content was then normalised to the weight of the wet tissue explants.…”
Section: Tropocollagen Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The marine sponge Chondrosia reniformis Nardo 1847 is a common marine demosponge, widely distributed along all the Mediterranean Sea and East Atlantic Ocean, where it inhabits both shallow and deep-water environments [ 1 ]. This demosponge lacks siliceous spicules and its body is entirely formed by a dense collagenous matrix with peculiar molecular features [ 2 , 3 , 4 ] with finely-regulated production [ 5 ]. This sponge is also characterized by good regenerative properties [ 6 ] whose molecular mechanisms have recently been described [ 7 ].…”
Section: Introductionmentioning
confidence: 99%